Structure and mechanism of action of the BRCA2 breast cancer tumor suppressor - Shahid,T; Soroka,J; Kong,EH; Malivert,L; McIlwraith,MJ; Pape,T; West,SC; Zhang,X (Nature Structural and Molecular Biology, 2014)
Mutations in BRCA2 increase susceptibility to breast, ovarian and prostate cancers. The product of human BRCA2, BRCA2 protein, has a key role in the repair of DNA double-strand breaks and interstrand cross-links by RAD51-mediated homologous recombination. Here, we present a biochemical and structural characterization of full-length (3,418 amino acid) BRCA2, alone and in complex with RAD51. We show that BRCA2 facilitates nucleation of RAD51 filaments at multiple sites on single-stranded DNA. Three-dimensional EM reconstructions revealed that BRCA2 exists as a dimer and that two oppositely oriented sets of RAD51 molecules bind the dimer. Single-stranded DNA binds along the long axis of BRCA2, such that only one set of RAD51 monomers can form a productive complex with DNA and establish filament formation. Our data define the molecular mechanism by which this tumor suppressor facilitates RAD51-mediated homologous-recombinational repair.